2015
DOI: 10.1002/pip.2612
|View full text |Cite
|
Sign up to set email alerts
|

40% efficient sunlight to electricity conversion

Abstract: Increasing sunlight conversion efficiency is a key driver for on-going solar electricity cost reduction. For photovoltaic conversion, the approach most successful in increasing conversion efficiency is to split sunlight into spectral bands and direct each band to a dedicated solar cell of an appropriate energy bandgap to convert this band efficiently. In this work, we demonstrate conversion of sunlight to electricity in a solar collector with an efficiency value above 40% for the first time, using a small 287-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 81 publications
(30 citation statements)
references
References 12 publications
0
30
0
Order By: Relevance
“…A final new result in Table is a new efficiency level of 40.6% for a concentrator submodule of 287 cm 2 aperture area, measured in outdoor testing by NREL for a 287 cm 2 split‐spectrum concentrator submodule fabricated by UNSW using commercial GaInP/GaInAs/Ge and Si cells manufactured by Spectrolab and SunPower, respectively .…”
Section: New Resultsmentioning
confidence: 99%
“…A final new result in Table is a new efficiency level of 40.6% for a concentrator submodule of 287 cm 2 aperture area, measured in outdoor testing by NREL for a 287 cm 2 split‐spectrum concentrator submodule fabricated by UNSW using commercial GaInP/GaInAs/Ge and Si cells manufactured by Spectrolab and SunPower, respectively .…”
Section: New Resultsmentioning
confidence: 99%
“…Gee et al made a two-junction GaAs/Si tandem cell with the efficiency of 31% under 347 suns [119], DiNetta et al made a two-junction Al x Ga 1-x As/Si tandem cell with the efficiency of 29.2% under 100 suns [120]. Green et al built a power tower concentrating system, they used a bandpass filter to split the concentrated sunlight into two parts, a three-junction GaInP/ GaInAs/Ge cell was used to absorb the reflected light, a Si back contact cell made by Sunpower company was used to absorb the transmitted light, the concentration ratio was 365 suns and the total efficiency reached 40.4%, which was the highest efficiency of the concentration systems of this kind [121]. Barnett et al proposed a six-junction tandem cell, which was consisted of a sub-cell with the bandgap of 2.4 eV, a GaInP sub-cell, a GaAs sub-cell, a Si sub-cell, a sub-cell with the bandgap of 0.95 eV and a sub-cell with the bandgap of 0.7 eV from top to down [95], they calculated the overall system efficiency and found that it could reach 53.5% under 20 suns.…”
Section: Silicon-based Multi-junction Cellmentioning
confidence: 99%
“…The VMJ cell has the smallest series resistance among all cells, its costs is low, its highest efficiency is 19.48% under very high concentration (1200 suns) [24] and will increase after optimizing the manufacturing process and device parameters. The silicon based multijunction cell is considered to be a possible "ultimate photovoltaic solution" [126], its highest efficiency is larger than 40% under high concentration (365 suns) although its costs is high [121].…”
Section: Summarization and Predictionmentioning
confidence: 99%
“…For the second power loss mechanism, the previous band‐pass filter directs out light from 880 to 1030 nm (1.41 to 1.206 eV) only (Figure ), suggesting that the Ge cell is still generating more photocurrent than the top two cells hence still dissipating some power. In fact, the wavelength range for the directed light can be extended further to ~1190 nm (1.04 eV) where the Ge cell can generate just matched photocurrent, unless it has significant defects resulting in too much bend in its I‐V curve before reaching its maximum power point voltage.…”
Section: Efficiency Loss Mechanisms and Potential For Further Efficiementioning
confidence: 99%
“…It uses not only built‐in filters to minimize luminescent coupling related losses and divide sunlight more appropriately, but also two cell stacks to better harness the entire solar spectrum and reduce some mismatch issues. The method is readily accessible to the industry in that a recent landmark result was demonstrated by commercial cells and the proposed Bragg‐type filters for the next‐generation version can be feasibly built into cells by industrial facilities.…”
Section: Significance and Conclusionmentioning
confidence: 99%